Cyanobacteria characteristics and methods for isolation and accurate identification of cyanotoxins: A review article - Yusof, Tengku Nadiah; Rafatullah, Mohd; Mohamad, Rohaslinda; Ismail, Norli; Zainuddin, Zarina; Lalung, Japareng (Hamadan University of Medical Sciences, 2017)
Cyanobacteria are bacteria found in different ecosystems, such as lakes and rocks. These bacteria, capable of photosynthesis, are important sources of oxygen. However, some cyanobacterial strains can produce toxins, which are harmful to humans and ani- mals. Therefore, collection of epidemiological and surveillance data on cyanobacterial toxins in the environment is vital to ensure a low risk of exposure to toxins in other organisms. For presentation of accurate data on environmental cyanobacterial toxins, it is essential to understand their characteristics, including taxonomy, toxin proteins, and genomic structures, and determine their environmental effects on bacterial populations and toxin production. Taxonomy, which is the scientific classification of organisms, is important in identifying species producing toxins. The structure of toxin proteins and their stability in the environment allow re- searchers to detect toxins with analytical methods and discuss their limitations. On the other hand, identifying toxins via molecular typing enables researchers to investigate toxic cyanobacteria by detecting toxin-encoding genes and toxin gene expression. Mean- while, environmental factors, such as nutrient level, light intensity, and biotic factors, allow researchers to predict the suitable time and location for accurate sampling. In this review, these cyanobacterial features, which are important for accurate detection of cyanobacterial toxins, will be discussed.